A smart marker-based indoor navigation system - Teoh, Zhen Quan (2024)

(untitled)
Blind people have difficulties in navigating indoor spaces, which may lead to accidents, inefficiency, and frustration. Normal individuals also face challenges in complex or unfamiliar indoor environments. This paper studies and compares the advantages and disadvantages of indoor navigation methods. We found that traditional navigation methods like GPS and Bluetooth beacons have limitations in terms of accuracy and user experience. Therefore, this project proposes a smart marker-based indoor navigation system to overcome these issues. The proposed system uses smartphone cameras for real-time marker recognition, and audio instructions for user support. The proposed system can create a map for a target indoor location, and the map data will be utilized for navigation and localization. The proposed system also employs algorithms to calculate the shortest path for navigation and estimate the user position for localization when the user scans a marker. The project aims to provide a low-cost, accurate, and real-time indoor navigation system and bridge the gap between traditional methods' limitations and user needs.